Efficacy of Metribuzin Doses on Physiological, Growth, and Yield Characteristics of Wheat and Its Associated Weeds - Javaid, Muhammad Mansoor; Mahmood, Athar; Bhatti, Muhammad Izhar Naeem; Waheed, Hasnain; Attia, Kotb; Aziz, Ahsan; Nadeem, Muhammad Ather; Khan, Naeem; Al-Doss, Abdullah A.; Fiaz, Sajid; Wang, Xiukang (Frontiers in Plant Science, 2022)
Weeds cause a serious constraint to wheat productivity. Chemical weed control is considered the most effective method to control weeds; however, a suitable dose and combination of herbicide with adjuvants play a vital role in controlling weeds and producing maximum wheat production. A field study was conducted to investigate the effectiveness of various doses of metribuzin alone or in combination with adjuvants [Bio-power (alkyl ether sulfates and sodium salts) and Ad-500 (fatty alcohol ethoxylate)] on the growth and yield of wheat and its associated weeds. Metribuzin at 175, 140, and 105 g a.i ha–1, each in combination with adjuvants (Bio-power or Ad-500) at 400 ml ha–1, were sprayed. A weedy check was also included as a control treatment. The wheat crop was infested with Fumaria indica, Melilotus indica, Anagallis arvensis, and Phalaris minor, and metribuzin with or without adjuvant was sprayed at two- to four-leaf stage of the weeds. The photosynthetic activity, weed population of each weed, and biomass of each weed was significantly affected by all herbicides along with the adjuvant. However, maximum inhibition of tested weeds was observed where metribuzin at 175 g a.i ha–1 + Bio-power at 400 ml ha–1 were sprayed. Metribuzin sprayed at 175 g a.i ha–1 with or without Bio-power recorded a maximum 1,000-grain weight, biological yield, and grain yield. Conclusively, metribuzin sprayed at 175 g a.i ha–1 + Bio-power at 400 at ml ha–1 have the potential to improve wheat yield by inhibiting weed growth, and Bio-power was superior to Ad-500 in improving the efficacy of metribuzin against weeds of wheat crop.